Frankie - Berthaud, Fabienne; Kruger, Diane; Gravelines, Jeannick; Wiggert, Christian (Alamode Film, 2011)
Fabienne Berthaud's gentle psychodrama Frankie probes the events that led to emotional crisis, mental breakdown, and psychiatric hospitalization for a fashion model. Nearing the age of 30, the titular ex-cover girl (Diane Kruger) is neither particularly young nor thin. She instead resides in an asylum in Blois, France, drugged out and in a semi-catatonic state. In flashback, Berthaud dramatizes the events that led to this predicament. Once active before the cameras and highly sought-after by agents, Frankie experienced a series of minor calamities including an on-set fight with a fashion photographer and the experience of accidentally hearing agents make disparaging remarks about her appearance, that collectively propelled her over the edge. Amid this world of grotesque artifice, the one bright spot seemed to be her ere-evolving friendship with the kindly driver of the modeling agency. Now, Frankie contents herself with institutional life and resists the thought of leaving and returning to the scabrousness of the real world ... Frankie [www.amazon.com]